Aromatic Sulfonium Polyoxomolybdates: Solid‐State Photochromic Materials with Tunable Properties. Issue 51 (10th November 2015) - Kumar, Ashwani; Devi, Manisha; Mamidi, Narsimha; Gonsalves, Kenneth E.; Pradeep, Chullikkattil P.
Abstract: A new aromatic sulfonium counter‐ion motif for polyoxometalate (POM) clusters with potential for structural and electronic fine‐tuning has been designed. Its two derivatives 4‐hydroxyphenyl dimethylsulfonium triflate (HPDST) and 4‐(allyloxy)phenyl dimethylsulfonium triflate (APDST) exhibit ionic liquid behaviors under ambient conditions. HPDST and APDST are used to develop a series of aromatic sulfonium POM hybrids (HPDS/APDS) n [XMo12 O40 ] (HPDS and APDS are the cations of HPDST and APDST, respectively; X=P or Si; n =3 or 4), which are tested for photochromic behavior. On exposure to UV light, these POM hybrids undergo color change from yellow to green/blue. The coloration kinetics half lives ( t 1/2 ) are less for APDS‐based hybrids than for HPDS‐based hybrids, suggesting that alkyl substitution on the phenolic group helps to fine‐tune the electron availability on the sulfonium moiety and hence to control the photochromic behavior of the POM hybrids. The t 1/2 values of these hybrids are considerably lower than those of the reported aliphatic sulfonium POM hybrids. We have also demonstrated the application of photoreduced POM hybrids as catalysts for the reduction of 4‐nitrophenol to 4‐aminophenol. Abstract : Lights on : A series of aromatic sulfonium polyoxometalate (POM) hybrids, a new class of materials with tunable photochromic behaviors, has been developed. The photoreduced POM hybrids were successfully tested as catalysts for the reduction of 4‐nitrophenol to 4‐aminophenol.